Cuaderno de imágenes. 'El soporte de la cultura (selección)' - Aledo, Jaime; Baena, Fernando; Blasco, Elena; Llanos, Cristina; Valcárcel Medina, Isidoro; Vallaure, Jaime (Escritura e Imagen, 2019)
El soporte de la culturaMadrid, 2012